2010
DOI: 10.1177/0894845309345671
|View full text |Cite
|
Sign up to set email alerts
|

Asian Indian College Students’ Science and Math Preferences: Influences of Cultural Contexts

Abstract: Cultural, immigrant, and prejudicial contexts influence minority students' preferences for college majors and their subsequent career development. Participants were Asian Indian immigrant college students as well as their parents. The early first-generation and late first-generation students were similar to each other in their major preferences; however, both groups had significantly greater preferences for science and math majors than the second-generation students. Parents' perceived prejudice and preference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 46 publications
2
46
0
1
Order By: Relevance
“…With the family forming a focal point of society in India (Roysircar, Carey, & Koroma, 2010) and adherence to one's duty towards family being a defining feature of work-related decisionmaking (Gupta & Tracey, 2005), this study examines the role of the family in the development of a calling orientation. Furthermore, the vocational literature does not clearly examine when a calling orientation is formed in relation to one's occupation and whether the sources of a calling are unique compared to that of a career (e.g.…”
mentioning
confidence: 99%
“…With the family forming a focal point of society in India (Roysircar, Carey, & Koroma, 2010) and adherence to one's duty towards family being a defining feature of work-related decisionmaking (Gupta & Tracey, 2005), this study examines the role of the family in the development of a calling orientation. Furthermore, the vocational literature does not clearly examine when a calling orientation is formed in relation to one's occupation and whether the sources of a calling are unique compared to that of a career (e.g.…”
mentioning
confidence: 99%
“…Second-generation Asian Indian immigrants reported lower preferences for science majors, higher engagement with the mainstream American society, and lower perceived prejudice than first-generation Asian Indian immigrant students. Similar to Louie (2001), Roysicar, Carey, and Koroma (2010) highlight that parents' perceived prejudice and preferences for science and math were instrumental in second-generation immigrants' inclinations toward choosing these majors, affi rming previous research that suggests parents and family are one of the most powerful infl uences on vocational behavior and career development (see Brown, 2004;Inman, Howard, Beaumont, and Walker, 2007;Sodowsky, 1991;Whiston and Keller, 2004). Stebleton (2010) examined career development in seven Black subSaharan African immigrant adult students attending an urban public fouryear university in the Midwest.…”
Section: Career Aspirations and Developmentmentioning
confidence: 84%
“…Another study examining college major preferences among Asian Indian immigrant college students and their parents, Roysircar, Carey, and Koroma (2010) found that Asian Indian immigrants' generational status, acculturation, perceptions of prejudice, and degree of parental infl uence were strongly related to their preferences for particular college majors. Second-generation Asian Indian immigrants reported lower preferences for science majors, higher engagement with the mainstream American society, and lower perceived prejudice than first-generation Asian Indian immigrant students.…”
Section: Career Aspirations and Developmentmentioning
confidence: 98%
“…Self-efficacy among Asian American adolescents can also be mediated by peer networks that can provide encouragement for more confidence in career decisions (Patel, Salahuddin, & O'Brien, 2008). Additionally, research has found that Asian American acculturation is positively correlated with perceived discrimination, which in turn can limit career choice possibilities to more common occupational fields (Roysircar, Carey, & Koroma, 2010).…”
Section: Literature Review: Career Development and Asian Americansmentioning
confidence: 99%